Marise Cremona e Joanne Scott (ed.) EU Law Beyond EU Borders. The Extraterritorial Reach of EU Law (London: Oxford University Press, 2019): Graça Canto Moniz (De Legibus - Law Journal, 2021)
Keywords: Extraterritoriality; European Union Law; Public International Law; Brussels effect.